Analisis Motivasi dan Hasil Belajar Siswa pada Pembelajaran IPAS - Elza Mardiana; Dodik Mulyono; Supriyanto Supriyanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aimed to determine the effect of the Discovery Learning model on students’ motivation and learning outcomes in grade III at MI Darussalam. The method used was an experimental research design involving two sample groups, namely an experimental group taught using the Discovery Learning model and a control group taught using conventional learning methods. The results indicate that the implementation of the Discovery Learning model has a positive effect on students’ motivation and learning outcomes compared to conventional learning. In conclusion, the Discovery Learning model is effective in improving motivation and learning outcomes of third-grade students at MI Darussalam. Keywords: Discovery Learning, Learning Outcomes, Motivation